Mixer Control System for Brick Making Based on PLC Omron CP1E-NA20DR-A - Setiawan, Eka Budi; Aji, Wahyu Sapto (Association for Scientific Computing Electrical and Engineering (ASCEE), 2022)
Bricks play a very important role in the construction of houses. No matter how beautiful a house is, without bricks, it cannot be said to be a house. With the development of architecture, bricks are not limited to the protection of the house, the role of bricks is now shifting towards a broader architectural design or construction. This research was conducted by designing hardware and software design and research materials. This hardware consists of several parts and ways of working in producing bricks, ranging from the frame as a support, control panel from PLC, pneumatic system, soil milling place, and 3-phase induction motor as a drive for the milling process so as to produce soil that is ready for molding. In programming the OMRON CP1E NA20DR-A PLC, supporting software is needed, namely CX-ONE software. CX-ONE software is designed on the software arranged according to the working principle, the volume of the mixture between 2 liters of soil and 2 liters of water using a delta circuit then a brick dough is produced that can be used properly. The existence of this tool is expected to make it easier to produce bricks.